GLP-1 receptor agonist-associated tumor adverse events: A real-world study from 2004 to 2021 based on FAERS - Yang, Zheng; Lv, Yuhuan; Yu, Meng; Mei, Mei; Xiang, Linyu; Zhao, Subei; Li, Rong (Frontiers in Pharmacology, 2022)
Abstract Background: GLP-1 Receptor Agonists (GLP-1RA) is demonstrated cardiovascular benefits, but the relationship between GLP-1RA and tumors is controversial. Recently, clinical trials reported that the malignancies reporting rate of semaglutide was higher than the control group. As real-world evidence on GLP-1RA-associated tumors risk is very limited, we explored the association of GLP-1RA and all types of neoplasms by mining the FDA adverse event reporting system (FAERS) database. Methods: FAERS data from the first quarter (Q1) of 2004 to the second quarter (Q2) of 2020 were extracted to conduct disproportionality analysis, which used by the proportional reporting ratios (PRR) to assess the relationship of GLP-1RA and all types of neoplasms. Then the details of disproportionate GLP-1RA-associated tumors cases were collected to analyze demographic characteristic. Results: A total of 8718 GLP-1RA-associated tumors were reported. Excluding cases with pre-existing tumors, other glucose-lowering drugs, and other GLP-1RA-related adverse events, diabetes cases with GLP-1RA as the main suspected drug were selected. GLP-1RA did not cause a disproportionate increase in all tumor cases (PRR 0.83) at the SOC level, and there was also no increase in most types of tumors associated with GLP-1RA at the HLGT/HLT levels. Significant signals were detected between GLP-1RA and certain tumors, including thyroid cancers [medullary thyroid cancer (PRR 27.43) and papillary thyroid cancer (PRR 8.68)], pancreatic neoplasms malignant (PRR 9.86), and islet cell neoplasms and APUDoma NEC (PRR 2.86). The combination of GLP-1RA with Dipeptidyl-peptidase IV inhibitors (DPP4i) perhaps caused the increased reporting rate in some tumors. Conclusions: Our study provides new real-world evidence for oncology safety information of GLP-1RA. Given the widely use of GLP-1RA, clinicians should be well informed about important potential adverse events. Our pharmacovigilance analysis also prompted clinicians to raise concerns about potential tumors-related adverse effects when combining GLP-1RA with DPP4i.